DESCRIPTIVE STUDY OF MISLEADING ADVERTISING BY SKINCARE INFLUENCERS AND ITS INFLUENCE ON INDONESIAN CUSTOMERS' PURCHASE INTENTION - Aidah, Sasangga
As influencer marketing has become more prevalent on social media platforms, the skincare industry has seen a significant shift in marketing strategies. Skincare influencers play a crucial role in shaping consumer behavior and influencing purchasing decisions. However, the transparency and credibility of skincare influencers have raised concerns, particularly in regard to misleading advertising practices. The purpose of this research is to understand the extend of influence those skincare influencers have on consumers' purchasing intention as well as the influence of misleading marketing on the Indonesian market. Through an examination of the perceptions, attitudes, and behaviors of Indonesian consumers, this research aims to describe the relationship between skincare influencers and customer behavior and explore the influence of misleading advertising practices. To achieve this objective, a descriptive study research approach was employed to gather data and descriptively analyze the topic. Primary data was collected through a survey targeting Indonesian respondents who have purchased skincare products and follow skincare influencers on social media. Additionally, secondary data was collected from various academic and non-academic sources related to the skincare industry and influencer marketing to augment the findings. The findings of the study suggest that these influencers hold a considerable sway over consumer choices, making their role in the market crucial for skincare brands. However, misleading advertising by influencers has negative consequences for influencers such as loss of following. This suggests that although consumers have some level of trust in skincare influencers, they can be deterred by misleading advertising tactics and transparency issues as customers value skincare influencers who disclose their relationships with brands and potential benefits received from product promotions. Influencers in the skincare industry who are open and honest about their relationships with brands and any potential benefits they may have received from product advertising are valued by their audience. In the skincare industry, maintaining transparency is essential to earning customers and fostering long-term brand-consumer relationships. The limitations of the study include a relatively small sample size and the use of self-reported data. Not only that, but it is also only a descriptive study, meaning that there is no further exploration of cause-and-effects. Further research could be to explore a more detailed analysis on the variables using statistical analysis to strengthen the results and find the cause-and effect relationship of the variables and have a larger and more diverse samples, as well as the use of more objective measures, could enhance the validity and generalizability of the findings. The originality and value of this research come from its contribution to the existing body of knowledge on the impact of misleading advertising in the skincare industry, particularly in the context of Indonesia. The study's unique insights into consumers' perceptions, attitudes, and actions around skincare influencers are made possible by its focus on the Indonesian market. This research has implications for skincare brands and influencers in Indonesia, highlighting the importance of transparency in advertising and building trust with customers and suggesting strategies to increase transparency and reduce the negative impact of misleading advertising by skincare influencers on social media in Indonesia. By providing these valuable insights, this research contributes to the ongoing efforts to understand and navigate the complex dynamics between influencers, brands, and consumers in the ever-evolving landscape of social media marketing within the skincare industry.